2022
DOI: 10.3390/life12050743
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying the Pain-Relieving Effects of Extracorporeal Shock Wave Therapy: A Focus on Fascia Nociceptors

Abstract: In recent years, extracorporeal shock wave therapy (ESWT) has received increasing attention for its potential beneficial effects on various bone and soft-tissue pathologies, yielding promising outcomes for pain relief and functional recovery. In fact, ESWT has emerged as an alternative, non-invasive, and safe treatment for the management of numerous musculoskeletal disorders, including myofascial pain syndrome (MPS). In particular, MPS is a common chronic painful condition, accounting for the largest proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 138 publications
1
23
0
2
Order By: Relevance
“…Both positive and negative pressure impulses provoke physical/mechanical consequences like absorption, reflection, refraction, and cavitation in the underlying treated tissues that are followed by numerous molecular and biological consequences, because of mechano-transduction. Indeed, shockwaves can activate various cell signaling pathways and induce the production of a variety of biomolecules [26] .…”
Section: Group (B) (N = 15) P-value* Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both positive and negative pressure impulses provoke physical/mechanical consequences like absorption, reflection, refraction, and cavitation in the underlying treated tissues that are followed by numerous molecular and biological consequences, because of mechano-transduction. Indeed, shockwaves can activate various cell signaling pathways and induce the production of a variety of biomolecules [26] .…”
Section: Group (B) (N = 15) P-value* Discussionmentioning
confidence: 99%
“…In the current study, the advantageous effect of shockwave therapy on reducing pain sensitivity and intensity along with recovering functional disability could be attributed to several mechanisms of action. shockwave therapy can relieve pain in musculoskeletal tissues via selectively destroying unmyelinated fibers, reducing neuropeptides related to pain, hyperstimulating nociceptors, modulating neurotransmission of pain, and reducing the levels of mediators of inflammation such as interleukins and matrixins [26,27] . Moreover, the shock waves produce micro-destruction, which causes micro-tearing of tissues with minimal or insufficient vascularization to promote revascularization via local growth factors production and stem cells mobilization, resulting in blood flow increase to these tissues and a subsequent reduction in muscular tension and tissue adhesions [28,29] .…”
Section: Group (B) (N = 15) P-value* Discussionmentioning
confidence: 99%
“…As demonstrated by several recent research articles [20][21][22][23][24][25][26][27][28][29], all these research activities led to many publications in the last four years in different peer-reviewed international journals, with a total Impact Factor of 22.4, and a total number of citations of 141 (35.25 mean citation per year) (source: Scopus.com; last update: 21 June 2022).…”
Section: Second Mission: Research Activitymentioning
confidence: 99%
“…Furthermore, different hypotheses have been proposed on the molecular mechanisms by which ESW treatment alleviates the pain in the musculoskeletal system [ 30 ], but so far, only the nerve component without the connective component has been considered [ 30 ]. However, Pavan et al [ 31 ], in considering the complex structure of deep fascia, reported that in myofascial pain, deep fascia could be subjected to two different kinds of alteration: (1) damage of loose component (rich in water and HA), affecting the sliding system between different layers and (2) damage of fibrous component, affecting the capacity of force transmission.…”
Section: Introductionmentioning
confidence: 99%